Активное демпфирование вынужденных резонансных изгибных колебаний изотропной вязкоупругой прямоугольной пластины с жестким защемлением торцов - Карнаухова, Т.В. (Видавничий дім "Академперіодика" НАН України, 2009)
Розв’язується задача про активне демпфування вимушених резонансних згинних коливань прямокутної в’язкопружної iзотропної пластини з жорстко затиснутими торцями. Вважається, що механiчне навантаження невiдоме i знаходиться з експериментальних показникiв сенсора. Методом Бубнова–Гальоркiна одержано формулу для рiзницi потенцiалiв, яку необхiдно пiдвести до актуатора для демпфування першої моди коливань пластини. Дослiджено вплив розмiрiв сенсора та актуатора, дисипативних властивостей i механiчних граничних умов на ефективнiсть активного демпфування коливань пластини. A problem of the active damping of forced resonant bending vibrations of a viscoelastic isotropic rectangular plate with the built-in edges is solved. We suppose that a mechanical load is unknown and have found it by the experimental data of a sensor. By the Bubnov–Galerkin method, a formula for a potential difference to damp the forced vibrations of a plate on the first mode is obtained. Influence of the dimensions of sensors and actuators, the dissipative material properties, and the boundary conditions on the effectiveness of the active damping of vibrations of the plate is investigated.